2005
DOI: 10.4161/cbt.4.2.1440
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2-mediated transport of photosensitizers: Potential impact on photodynamic therapy

Abstract: In photodynamic therapy (PDT), a tumor-selective photosensitizer is administered followed by activation of the photosensitizer by exposure to a light source of a given wavelength. This, in turn, generates reactive oxygen species that induce cellular apoptosis and necrosis in tumor tissue. Based on our earlier finding that the photosensitizer pheophorbide a is an ABCG2 substrate, we explored the ability of ABCG2 to transport photosensitizers with a structure similar to that of pheophorbide a. ABCG2-overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
162
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(168 citation statements)
references
References 33 publications
4
162
0
2
Order By: Relevance
“…Robey et al reported that the expression of atP-binding cassette (aBc) transport proteins, which render tumor cells resistant to chemotherapeutic drugs, decreases the accumulation of photosensitizers and causes resistance to PDt (41). We have also previously reported that BcrP, a member of the aBc transporter family, decreases the accumulation of Photofrin and may be a molecular determinant (29).…”
Section: Discussionmentioning
confidence: 99%
“…Robey et al reported that the expression of atP-binding cassette (aBc) transport proteins, which render tumor cells resistant to chemotherapeutic drugs, decreases the accumulation of photosensitizers and causes resistance to PDt (41). We have also previously reported that BcrP, a member of the aBc transporter family, decreases the accumulation of Photofrin and may be a molecular determinant (29).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several TKIs such as imatinib, gefitinib, and nilotinib are BCRP substrates (1,13). A variety of photosensitizers including pheophorbide A, protoporphyrin IX, and related compounds are also BCRP substrates, suggesting that BCRP is a possible cause of cellular resistance to photodynamic therapy (14).…”
Section: Bcrp Substratesmentioning
confidence: 99%
“…In addition to other known porphyrin ABCG2 substrates that are used for photodynamic therapy (Robey et al, 2004(Robey et al, , 2005, we investigated Pp-18 (structure shown in Fig. 3A) as a potential new porphyrin substrate of ABCG2 by efflux studies with ABCG2-overexpressing sublines ( Fig.…”
Section: Functional Comparison Of Human and Murine Abcg2mentioning
confidence: 99%